Transformasi sosial masyarakat pedesaan di era milenial - Syahrani, Andini (Maliki Interdisciplinary Journal, 2024)
The social transformation of rural communities in the millennial era encompasses changes in structure, values, and social interactions due to the influences of modernization, digital technology, and the currents of globalization. In this era, villages are no longer lagging behind in the development of information and technology, but are starting to move towards modernization and integrating with the digital world. The adoption of technologies such as the internet and social media is changing communication methods, consumption patterns, and access to information and services. The younger generation in rural areas is starting to play a role as agents of change, driving innovation and digital entrepreneurship through various platforms. Moreover, social interactions are undergoing a shift, where virtual networks complement and sometimes replace traditional face-to-face relationships. This transformation impacts economic, social, and cultural aspects; generating new opportunities, challenges, and dynamics that need to be managed to remain in harmony with local wisdom and long-standing values. In this writing, a literature study method is used where the author collects data from research results as well as sources from journals, articles, and internet sites.